The Vitality of Javanese Language in the Bakery Register - Ni’mah Dini Sadida; Sumarlam Sumarlam; FX Sawardi (Universitas Muhammadiyah Semarang, 2023)
The Javanese language treasures in the context used in the bakery sector act as a means of social interaction in the baker group. The conversational symbols present in the baker group have their characteristics. The existence of utterances by the baker community certainly has a basis and meaning. The meaning of certain words requires a view of the context of the situation contained in the communication. This research is needed to reveal a language that is unique or special in its use, namely in the bakery sector. The method used in this research is descriptive qualitative. The research data is in the form of speech and text of customer orders. The data source is in the form of oral speech through recordings of the baking group, and the written data source is in the form of a list of orders via social media platforms. The data collection techniques used include (1) tapping, (2) free-to-view, free of involvement, and (3) recording and noting. Data analysis technique is descriptive analysis with using an interactive analytical model. The results of this study indicate the novelty of using a unique Javanese vocabulary in the realm of bakery. Javanese lexicon language can use for the following purposes: (1) the process of making bread, (2) the shape and type of bread, (3) buying and selling transactions, (4) mentioning the price of bread, (5) and the quality of bread